2021
DOI: 10.3389/fmed.2021.721442
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Current Clinical Applications of Anterior Segment Optical Coherence Tomography Angiography

Abstract: Optical coherence tomography angiography (OCTA) is the most relevant evolution based on optical coherence tomography (OCT). OCTA can present ocular vasculature, show detailed morphology for assessment, and quantify vessel parameters without intravenous dye agent. Research on the anterior segment OCTA (AS-OCTA) is only in its initial phase, and its advances in clinical diagnosis and treatment efficacy evaluations require a detailed comparison to traditional imaging methods. In this review of AS-OCTA, we summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…The main drawback of switching scan configurations is the time gap for changing the settings. Recently, Luo et al have demonstrated an SS-OCT prototype that utilizes a single source and a single detection channel for sequential imaging ( 192 ).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The main drawback of switching scan configurations is the time gap for changing the settings. Recently, Luo et al have demonstrated an SS-OCT prototype that utilizes a single source and a single detection channel for sequential imaging ( 192 ).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The major drawback of OCTA when compared to the traditional angiography tools lies in its inability to identify the flow characteristics and thus, patterns of leakage, the difference between afferent and efferent systems, etc. cannot be captured with OCTA [30,31]. In the context of ocular burns, this is relevant as images from OCTA may not distinguish vasospasm from true ischemia and thus caution must be exercised during interpretation of OCTA scans.…”
Section: Comparison With Fluorescein Angiography (Fa) and Indocyanine...mentioning
confidence: 99%
“…The OCT machines are devised to image the structure and functional blood flow of the retina and the choroid. To do so, a special adaptor lens attachment is usually required to perform anterior segment angiography; however, the image acquisition can also be carried out by manually adjusting the focus [31,34]. In such cases, the external lens is very close to the patient's eye and care has to be taken to avoid accidental trauma [3].…”
Section: Image Acquisitionmentioning
confidence: 99%
“… 16 , 17 In recent years, anterior segment OCTA (AS-OCTA) has gained acceptance, and its value has been validated in various anterior segment diseases, including glaucoma filtering surgery (GFS) and minimally invasive glaucoma surgery (MIGS). 18 25 Previous studies found that superficial vascular density (SVD) in the bleb area was more associated with postoperative IOP and surgical outcome than IBAGS and MBGS. 22 , 26 , 27 However, none of them have provided a joint analysis of the vascular and morphological parameters.…”
Section: Introductionmentioning
confidence: 99%